2009
DOI: 10.1111/j.1365-2575.2007.00269.x
|View full text |Cite
|
Sign up to set email alerts
|

Understanding dynamics between initial trust and usage intentions of mobile banking

Abstract: Mobile banking is an emerging application of mobile commerce that could become an additional revenue source to both banks and telecom service providers. It is a form of service convergence enabled by innovative technologies. Despite the alleged benefits of mobile banking, its acceptance has been short of industry expectations. One plausible explanation may be consumers' initial lack of trust in available services. The objective of our research is to reveal the mechanisms associated with the initial formation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
529
2
21

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 686 publications
(604 citation statements)
references
References 69 publications
(188 reference statements)
52
529
2
21
Order By: Relevance
“…Research has found that industry trust plays a significant role in the adoption of innovative services such as web related technologies (Pavlou & Gefen, 2004;Kim et al, 2009;Li et al, 2011); this is most likely due to the uncertain nature of the online environment, reinforced by the lack of physical interaction and anonymity involved in the medium (Ratnasingam, 2005).…”
Section: Antecedents Of Technology Readinessmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has found that industry trust plays a significant role in the adoption of innovative services such as web related technologies (Pavlou & Gefen, 2004;Kim et al, 2009;Li et al, 2011); this is most likely due to the uncertain nature of the online environment, reinforced by the lack of physical interaction and anonymity involved in the medium (Ratnasingam, 2005).…”
Section: Antecedents Of Technology Readinessmentioning
confidence: 99%
“…The role of industry trust is becoming increasingly important in online contexts (McKnight et al 2002;Pavlou & Gefen, 2004;Kim, Shin & Lee, 2009). Retailers newly adopting this channel as demand for online shopping increases need assurances from service providers about its viability and reliability.…”
Section: Industry Trustmentioning
confidence: 99%
“…And as we have discussed in previous section, the influencing effects of effort expectancy and trust on VC re-usage intentions might become weak as members are familiar with a VC. However, Kim, Shin and Lee (2009) found that the perception of initial trust is vital in promoting personal intention to use mobile banking services. Gefen et al (2003) also found that potential customers (inexperienced customers) were influenced by their trust in the e-vendor.…”
Section: Contributionsmentioning
confidence: 99%
“…Trust is a long-term relationship, and transaction is a critical factor (Chaudhuri and Holbrook, 2001).Trust is also a critical point for e-commerce there are a lack of proven guarantees that the e-vendor will not engage in harmful opportunistic behaviors (Gefen, Straub, and Boudreau, 2000;Kollock, 1999;Reichheld and Schefter, 2000).Such behaviors include unfair pricing, conveying inaccurate information, violating privacy, unauthorized use of credit card information, and unauthorized tracking of transactions (Gefen, Karahanna, and Straub, 2003).A trust relationship benefits the e-vendor (Reichheld and Schefter, 2000).Prior literature shows TAM as a theoretical frame work a critical factor that reflects the user's security and privacy concerns in the customer acceptance of Internet banking (Wang, Wang, Lin, and Tang, 2003).Therefore, one reason to not use mobile banking is a lack of trust (Lin, 2011;Kim et al, ISSN 1941-899X 2017 2009; Lee and Chung, 2009). Competence, benevolence, integrity and predictability of trusting beliefs can generate trust (McKnight, Cummings, and Chervany, 1998).…”
Section: Trust and Perceived Risk Attitudementioning
confidence: 99%
“…But some people said not to worry at all (24.7%) when they use mobile banking (TWNIC, 2016).The data show that most mobile banking users have existing concerns about privacy and security. Many bank customers have a lack of trust, lack of controllability, security issue, and concern privacy of electronic banking (Susanto, 2016;Kim, Shin, and Lee, 2009;Lee and Chung, 2009;Luarn and Lin, 2005).Therefore, there are many banking customers that still prefer ATM banking services (Shih and Fang, 2006).Mobile banking firms should emphasize the importance of security, safety, reliability and convenience (Lin, 2011).However, banking firms offer mobile banking service that not only build a safe transaction environment, but also focus on the security of personal information collection and privacy mechanism. Previous studies only discussed the trust perceived and intention of usage mobile banking (Gumussoy, 2016;Gu, Lee, and Suh, 2009) or the concern privacy and personal perceived of adopt Internet banking (Susanto, 2016;Pikkarainen, Pikkarainen, Karjaluoto, and Pahnila, 2004).Few studies have focused on the issue of privacy mechanism influence concerns for personal information, trust perceived, and risk perceived attitude.…”
Section: Introductionmentioning
confidence: 99%